The development of learning video media on sequence and series materials - Kamalia, Kamalia; Lusiana, Lusiana; Destiniar, Destiniar (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to produce a video media product for learning the material of sequences and series for class XI students that is valid, practical, and has potential effects. The method used in this research is the research and development method with the ADDIE development procedure, which consists of five stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The instruments used to obtain research data are in the form of expert validation questionnaires, student response questionnaires, and test sheets. The results of the assessment from the experts obtained a percentage score of 84.81% so that the learning video was declared